(untitled) (ENTHYMEMA, 2013)
The following material is the typescript version of a discussion on The 3rd ENN Conference in Paris, held by two of its participants. The discussion was carried in the format of a Skype session on September 21, 2013. It was initiated and structured by Ludmila Tataru within the framework of the state assignment of the Russian Ministry of Education and Science.